Analisis Kesalahan Newman Dalam Menyelesaikan Soal Cerita Materi Turunan Pada Siswa Kelas XII - Fitri, Nurul Wahidatul; Subarinah, Sri; Turmuzi, Muhammad (Mandalika Mathematics and Educations Journal, 2019)
This study was conducted to determine each character of Newman’s error and its percentage on student class XII MAN 2 Mataram in academic year 2018/2019. Students’ errors found through analyzing students answer in solving story question material of derivative. Based on the result of data analyzed and interview which has been done, it showed that no one of the students can answer all of the questions correctly. The population of this study was 215 students and the sample was 32 students. Analysis technique used for this study was descriptive analysis. Based on the result of the data, it can be found that reading error was on the lowest percentage that is 23%. Error in comprehension and transformation was on the medium percentage those are 44% and 49%. Error in processing skill was on the lower percentage that is 29%. The last is encoding error was on the highest percentage that is 78%.AbstrakPenelitian ini bertujuan untuk mengetahui kriteria masing-masing jenis kesalahan Newman dan persentasenya pada siswa kelas XII MAN 2 Mataram tahun pelajaran 2018/2019. Kesalahan-kesalahan siswa diketahui melalui analisis terhadap jawaban siswa dalam menyelesaikan soal cerita turunan. Berdasarkan hasil analisis data dan wawancara yang telah dilakukan menunjukkan bahwa tidak ada siswa yang dapat menjawab dengan benar semua soal yang telah diberikan. Populasi penelitian sebanyak 215 siswa dengan sampel penelitian 32 siswa. Teknik analisis yang digunakan adalah analisis deskriptif. Dari hasil penelitian diperoleh, bahwa kesalahan membaca berada dalam kriteria sangat rendah dengan persentase 23%. Kesalahan memahami soal dan transformasi berada dalam kriteria sedang dengan persentase berturut-turut 44% dan 49%. Kesalahan keterampilan proses berada dalam kriteria rendah dengan persentase 29%. Dan kesalahan penulisan jawaban berada dalam kriteria sangat tinggi dengan persentase sebesar 78%.